The role of Islamic financial literacy towards adoption of Islamic banking products and services: a systematic literature review - Kaweesa, Yusuf; Rosman, Romzie (Labuan Faculty of International Finance, Universiti Malaysia Sabah, 2024)
Following the increased demand for Islamic banking products and services in different economies, research on the effect of Islamic financial literacy in the adoption of Islamic banking products and services has increased in recent years. The purpose of this study is to identify and explore the role of Islamic financial literacy towards the adoption of Islamic banking products and services as it has not been categorically addressed in the prevailing literature so far. The study used a systematic literature review following the PRISMA protocol to execute the analysis of the review. The results identified awareness, enhancement of the intention to use, directing financial decision making and modelling financial behaviour as the key roles of Islamic financial literacy towards the adoption of Islamic banking products and services. The study helps in directing future research on Islamic financial literacy towards understanding it in line with the identified roles.